6-2(-5g-6)=

Simple and best practice solution for 6-2(-5g-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(-5g-6)= equation:


Simplifying
6 + -2(-5g + -6) = 0

Reorder the terms:
6 + -2(-6 + -5g) = 0
6 + (-6 * -2 + -5g * -2) = 0
6 + (12 + 10g) = 0

Combine like terms: 6 + 12 = 18
18 + 10g = 0

Solving
18 + 10g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 10g = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 10g = 0 + -18
10g = 0 + -18

Combine like terms: 0 + -18 = -18
10g = -18

Divide each side by '10'.
g = -1.8

Simplifying
g = -1.8

See similar equations:

| 9x-5(2x-1)=-6 | | 2-3x+9x= | | 9x-3(2x-1)=-6 | | 2a+5x-3a= | | (x-2)2+(y+3)2=4 | | 6m+11=5m+8 | | -340+500x=-3677+-30x | | 2(m-8)=5m+26 | | f(x)=-x^2+8x-2 | | -10=-3x+x+10 | | .5x+4=10 | | 78y+2+7=2y+3 | | 2lnx-4=0 | | s(s^2+s-56)=0 | | 3a+8=2a+12 | | 6=10-5+2x+7x | | 7(h+4h)+3=4h+4h+3 | | X^2+5x=8x+40 | | 5w+6x=15m | | 11W=4730 | | 17q+45q+23=12q+2 | | g(x+h)=-5x-9 | | 34m-4=65 | | g(x+h)g(x)=-5x-9 | | 4(3x+6)=2(x-7) | | 2x-(-5)=17 | | 5s+25=1s+3 | | 16=4x-7x+10 | | -3=4x-5x-2 | | 8sin(3x)=2 | | 27=2x+2x+7 | | 3w+3+3+3w+4=3w+3w+3 |

Equations solver categories